Widespread Neogene volcanism on Central Kerguelen Plateau, Southern Indian Ocean. Issue 4 (18th May 2016) - Duncan, R. A.; Falloon, T. J.; Quilty, P. G.; Coffin, M. F.
ABSTRACT: We report new age determinations and compositions for rocks from 18 dredge hauls collected from eight submarine areas across Central Kerguelen Plateau (CKP). Sea knolls and volcanic fields with multiple small cones were targeted over a ∼125 000 km 2 region that includes Heard and McDonald Islands. Large early Miocene (22–16 Ma) sea knolls rise from the western margin of the CKP and are part of a NNW–SSE line of volcanic centres that lie between Îles Kerguelen and Heard and McDonald Islands. These are probably related to hotspot activity now underlying the Heard Island area. We see evidence of much younger activity (5 Ma to present) in volcanic fields to the north of, and up to 300 km NE of, Heard Island. Compositions include basanite, basalt and trachybasalt, which are broadly similar to plateau lava flows from nearby Ocean Drilling Program Site 1138, lower Miocene lavas at Îles Kerguelen, dredged rocks from the early Miocene sea knolls, and Big Ben lavas from Heard Island. Geochemical data indicate decreasing fractions of mantle source melting with time. We propose that a broad region of the CKP became volcanically active in Neogene time owing to incubation of plume material at the base of the relatively stationary overlying plateau. The presence of pre-existing crustal faults gave access for melts from the Heard mantle plume to rise to the surface.